THE ENGLISH DEPARTMENT STUDENTSâ PERCEPTION ON ENTREPRENEURSHIP EDUCATION - Tristiana, Novita Eka (JURNAL SMART, 2017)
AbstractÂ The aim of this research is to know what the English Department studentsâ perceptions are on the entrepreneurship. TheÂ  research was conducted at the sixth semester of STKIP Muhammadiyah Pringsewu which the participant were the studentsÂ  who studiedÂ  Entrepreneurship. There were 50 students who were involved in this research. But, in this research, the researcher only took 5 students as the representative of the students since the design of this research was qualitative research design. The data collecting techniques used in this research were think- aloud protocol, interview and observation. In analyzing the data, the researcher did some activities such as; describing, classifying and connecting. The finding of the research showed that the students have positive perception on entrepreneurship and the students also think that entrepreneurship is important seen from the usage perception.Keywords: Perception, Entrepreneurship and English Department students.